Withdrawal of Antidementia Drugs in Advanced Dementia (WADAD): a randomized clinical trial and cost-utility analysis - Rute Filipa Crespo Gonçalves (2022)
Introduction:Dementia is a major public health concern due to its increasing prevalence, substantial caregiver burden, and high financial costs. Currently, antidementia drugs provide only symptomatic effect. The subject of prescribing these drugs in advanced stages is a matter of substantial debate, with different countries making distinct recommendations. Methods:We conducted a pilot, pragmatic, unicentric, parallel randomized (1:1) open clinical trial with blinded assessors to assess the safety and efficacy of withdrawing antidementia drugs in patients with severe dementia. Functional and behaviour outcomes, quality of life indexes (both for the patient and their caregivers), financial costs and adverse events were evaluated for a period of 24 weeks. Results:14 patients were included in the study. Patients assigned to drug continuation showed better functional performance of activities of daily living at week 12 and better quality of life at week 24 as assessed by EQ-5D. Rate of adverse events and mean time to serious adverse event/withdrawal was similar in both treatment groups. Overall, caregivers considered the patient's condition to be unchanged during the follow-up and the rate of severe neuropsychiatric symptoms did not differ between groups. Despite costs were not statistically different, the incremental cost-utility ratio supports treatment continuation, given a higher cost and lower QALY gain in the withdrawal group. Discussion:Our study suggests that continuing antidementia drugs in people with advanced Alzheimer's disease may provide better functional outcomes and quality of life. The interpretation of our findings needs to be carefully considered in light of reduced sample size, absence of a placebo-controlled group and subjective nature of the outcomes evaluated. Conclusion:Our study improves the evidence regarding the withdrawal of antidementia drugs in advanced dementia. It is the first of its kind in Portugal to provide insight into quality of life and financial costs in patients and caregivers. We consider that, as a pilot study, our work could lay the foundations for further studies with higher sample sizes and longer follow-up periods.